Tantangan dan Solusi Penerapan E-Government di Indonesia - Kennedy, Alexander; Surya, William Hartato; Wartoyo, Franciscus Xaverius (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2024)
This study describes the challenges and solutions in implementing e-government in Indonesia using a qualitative and case study approach. The study aims to understand the policy framework underpinning the implementation of e-government in Indonesia, identify the challenges faced, and develop practical recommendations to improve the effectiveness and efficiency of e-government. This research involves the analysis of official documents such as government policies, reports from official government and international agencies, legislation, and other related documents. Data are analyzed qualitatively using thematic analysis methods by classifying and identifying the main themes from the analyzed documents. The validity of the findings is confirmed through data triangulation by comparing relevant official documents and by considering case studies from other countries that have successfully implemented e-government as comparative material. The results show that the main challenges in implementing e-government in Indonesia include the digital divide, limited internet access, high costs, low public awareness, language and literacy issues, privacy and data security concerns, and resistance to change. Based on these findings, practical recommendations are formulated, such as enhancing digital infrastructure, providing education and training for the public, and strengthening regulatory frameworks to support more effective and efficient e-government implementation in Indonesia.